A gEUD‐based inverse planning technique for HDR prostate brachytherapy: Feasibility study. Issue 4 (13th March 2013) - Giantsoudi, D.; Baltas, D.; Karabis, A.; Mavroidis, P.; Zamboglou, N.; Tselis, N.; Shi, C.; Papanikolaou, N.
Abstract : Purpose: : The purpose of this work was to study the feasibility of a new inverse planning technique based on the generalized equivalent uniform dose for image‐guided high dose rate (HDR) prostate cancer brachytherapy in comparison to conventional dose‐volume based optimization. Methods: : The quality of 12 clinical HDR brachytherapy implants for prostate utilizing HIPO (Hybrid Inverse Planning Optimization) is compared with alternative plans, which were produced through inverse planning using the generalized equivalent uniform dose (gEUD). All the common dose‐volume indices for the prostate and the organs at risk were considered together with radiobiological measures. The clinical effectiveness of the different dose distributions was investigated by comparing dose volume histogram and gEUD evaluators. Results: : Our results demonstrate the feasibility of gEUD‐based inverse planning in HDR brachytherapy implants for prostate. A statistically significant decrease in D10 or/and final gEUD values for the organs at risk (urethra, bladder, and rectum) was found while improving dose homogeneity or dose conformity of the target volume. Conclusions: : Following the promising results of gEUD‐based optimization in intensity modulated radiation therapy treatment optimization, as reported in the literature, the implementation of a similar model in HDR brachytherapy treatment plan optimization is suggested by this study. The potential of improved sparing of organs at risk was shown for various gEUD‐based optimization parameter protocols, which indicates the ability of this method to adapt to the user's preferences.